Cycle Related Graphs on Square Difference Labeling (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, we prove that the graphs cycle  with parallel chords,  of , Durer-graph, Moser-spindle, Herchel graph are Square difference graph (SDG).